2019
DOI: 10.1038/s41467-019-13422-9
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl-rich macromolecules enable the bio-inspired synthesis of single crystal nanocomposites

Abstract: Acidic macromolecules are traditionally considered key to calcium carbonate biomineralisation and have long been first choice in the bio-inspired synthesis of crystalline materials. Here, we challenge this view and demonstrate that low-charge macromolecules can vastly outperform their acidic counterparts in the synthesis of nanocomposites. Using gold nanoparticles functionalised with low charge, hydroxyl-rich proteins and homopolymers as growth additives, we show that extremely high concentrations of nanoparti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(66 citation statements)
references
References 86 publications
(123 reference statements)
1
64
1
Order By: Relevance
“…However, since the stress tensor of a supercell is just the volume-average of the atomic virials, it is common to average the atomic virials over an appropriate local volume to produce a local stress field. Branicio and Srolovitz 22 presented a general method for this, later applied to titania nanoparticles 23 and calcite defects, 24,25 that involves calculating the time averaged atomic virial tensors hW ab i i , and multiplying their value by a normalised smearing function P(…”
Section: Calculating the Local Stress Fieldmentioning
confidence: 99%
“…However, since the stress tensor of a supercell is just the volume-average of the atomic virials, it is common to average the atomic virials over an appropriate local volume to produce a local stress field. Branicio and Srolovitz 22 presented a general method for this, later applied to titania nanoparticles 23 and calcite defects, 24,25 that involves calculating the time averaged atomic virial tensors hW ab i i , and multiplying their value by a normalised smearing function P(…”
Section: Calculating the Local Stress Fieldmentioning
confidence: 99%
“…1 In recent years, the most widely used diffusionbased method, the ammonia diffusion method (ADM), 2,3 has been utilized to synthesize calcium carbonate minerals for addressing questions in various research fields. The investigation of nucleation and crystal growth processes, 4,5 additive effects on the formation of calcium carbonate, [6][7][8][9] the synthesis and characterization of nanocomposites, [10][11][12][13][14][15][16] investigations regarding changes in material properties of crystals, 17 as well as syntheses of composite particles for potential use in cancer therapy 18 have been carried out using ADM. In addition, ADM has been used to investigate and characterize polymer-induced liquid precursor (PILP) phases.…”
Section: Introductionmentioning
confidence: 99%
“…71,72 For this purpose, considerable effort has been made to unravel the mechanisms by which additives become incorporated within calcite single crystals. 24,29,[73][74][75] These studies have demonstrated that occlusion is governed by the binding affinity of the additive to the surface of the growing crystal. Efficient occlusion is achieved when an additive binds strongly enough to binding sites on the crystal surface (i.e., kinks and step edges) such that the residence time on the crystal surface exceeds the time taken for steps to propagate around the particles, but not so strongly that crystal growth is inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Crystal growth is a traditional method of purication, and as such co-precipitation with bioactive molecules typically leads to low levels of occlusion. [24][25][26] However, we have recently shown that it is possible to achieve high loadings of inorganic nanoparticles [27][28][29] and polymer nano-objects [30][31][32] provided that the surfaces are functionalized with polymer chains or proteins such that the particles are both colloidally stable in the crystal growth solution and bind to the crystal surface. Notably, polymer vesicles containing small uorescent dyes 33 and silica particles 33,34 have been occluded, but the highly permeable vesicle membrane precludes their general use as effective carriers.…”
Section: Introductionmentioning
confidence: 99%